Knowledge, attitude, and practice of parents regarding Vitamin A supplementation to children in Benghazi, Libya - Abdulmalek, Lubna; Benkhaial, Fatma (Ibnosina journal of medicine and biomedical sciences, 2018)
Background: According to the World Health Organization, Vitamin A deficiency can cause immune system depression in about 130 million preschool children and 7 million pregnant women mostly in developing countries and cause mortality risk up to 20%–30%. Objectives: We aimed to evaluate the knowledge, attitude, and practice of parents in Benghazi regarding the Vitamin A campaign. Subjects and Methods: A cross-sectional descriptive study of 1390 parents attending maternal and child health clinics and pediatric clinics at six main polyclinics, in Benghazi in April and May 2018. Results: Most of the parents were younger than 40 years (71%). Mothers constitute 68% of the study population and 52% of the children were male. Half of the parents had higher education. Only 40% of the parents were having good knowledge about the benefits and food sources of Vitamin A. The coverage rate of Vitamin A supplementation among under-five children in the study was 66%. The main reason for not giving their children Vitamin A supplementation in this study was the lack of awareness of the campaign during the previous year. However, 88% of the interviewed parents had a positive attitude of regiving Vitamin A to their children in the next campaign. Conclusions: The overall knowledge level of Vitamin A among the parents was relatively low; hence, more efforts are needed to promote awareness about Vitamin A supplementation.